6y = x + 5

Question

Asked 4/5/2014 11:34:23 AM

Updated 4/6/2014 9:08:02 AM

7 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [4/6/2014 8:40:27 AM]

= 7x + 28 + 42y

Alaked|Points 50|

onlydbest24|Points 185|

OxTornado007|Points 6899|

JuggyDC|Points 80|

alfred123|Points 11266|

ritaswanski|Points 100|

leo4797|Points 10|

jher000|Points 8066|

aljerald03|Points 168|

brenda143|Points 141|

csnyder83|Points 1610|

jher000|Points 8066|

karenlohman|Points 120|

emdjay23|Points 3298|

Polio123|Points 357|

Ashnicole49|Points 104|

Onyhon|Points 174|

wiwit|Points 688|

bankai123|Points 0|

ritaswanski|Points 100|

Polio123|Points 357|

bankai123|Points 0|

brenda143|Points 141|

Question

Asked 4/5/2014 11:34:23 AM

Updated 4/6/2014 9:08:02 AM

7 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [4/6/2014 8:40:27 AM]

Rating

3

The equation in point-slope form for the line through the given point (8, 3); with the given slope m = 6 is D. y - 3 = 6(x - 8)

Added 4/6/2014 8:41:53 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:45 AM]

3

The solution of the system y = –3x + 2; y = –3x + 4 is C. no solutions.

The lines with same slope are parallel and there is no intersecting point (solution).

The lines with same slope are parallel and there is no intersecting point (solution).

Added 4/6/2014 8:44:15 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:45 AM]

3

The solution the system x = -4y + 4; 2x + 8y = 8 has is: C. infinitely many solutions.

x = -4y + 4 (equation 1), can be rewritten as x + 4y = 4

2x + 8y = 8 (equation 2), devided by 2 on both sides: x + 4y = 4

Therefore, equation 1 and 2 are the same line, and there are infinite solutions to the line system.

x = -4y + 4 (equation 1), can be rewritten as x + 4y = 4

2x + 8y = 8 (equation 2), devided by 2 on both sides: x + 4y = 4

Therefore, equation 1 and 2 are the same line, and there are infinite solutions to the line system.

Added 4/6/2014 8:49:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:46 AM]

3

3x – 4y = 9

–3x + 2y = 9

Adding the above equations: -2y = 18, y = 18/-2 = -9

3x – 4(-9) = 9

3x + 36 = 9

3x = 9 - 36 = - 27

x = -27/3 = -9

The solution for the sytem of equations 3x – 4y = 9; –3x + 2y = 9 is D. (–9, –9)

–3x + 2y = 9

Adding the above equations: -2y = 18, y = 18/-2 = -9

3x – 4(-9) = 9

3x + 36 = 9

3x = 9 - 36 = - 27

x = -27/3 = -9

The solution for the sytem of equations 3x – 4y = 9; –3x + 2y = 9 is D. (–9, –9)

Added 4/6/2014 8:54:19 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:47 AM]

3

3x – 4y = –24 (equation 1)

x + y = –1 multiply 4 on both sides: 4x + 4y = -4 (equation 2)

Adding up equation 1 and equation 2 we get: 7x = - 28

so x = -28/7 = -4;

(-4) + y = –1,

y = - 1 + 4 = 3

The slotion for the system of equations 3x – 4y = –24; x + y = –1 is B. (–4, 3)

x + y = –1 multiply 4 on both sides: 4x + 4y = -4 (equation 2)

Adding up equation 1 and equation 2 we get: 7x = - 28

so x = -28/7 = -4;

(-4) + y = –1,

y = - 1 + 4 = 3

The slotion for the system of equations 3x – 4y = –24; x + y = –1 is B. (–4, 3)

Added 4/6/2014 9:00:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:48 AM]

3

The solution of the system y = x + 5; y = –5x – 1 is (-1, 4)

y = x + 5

y = –5x – 1

Replace y in the second equation with the first one;

x + 5 = –5x – 1

x + 5x = - 1 - 5

6x = -6

x = -1

y = -1 + 5 = 4

y = x + 5

y = –5x – 1

Replace y in the second equation with the first one;

x + 5 = –5x – 1

x + 5x = - 1 - 5

6x = -6

x = -1

y = -1 + 5 = 4

Added 4/6/2014 9:05:11 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:49 AM]

3

The solution of the system y = x + 6; y = 2x is A. (6, 12)

replace y with 2x in the equation y = x + 6 we get: 2x = x + 6, so x = 6;

y = 2(6) = 12

replace y with 2x in the equation y = x + 6 we get: 2x = x + 6, so x = 6;

y = 2(6) = 12

Added 4/6/2014 9:08:02 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [4/6/2014 10:19:50 AM]

What are the solutions of the inequality? Check the solutions. 4x + 6 –3
B. x –6 **Weegy:** B. x **User:** What are the solutions of the compound inequality? Graph the solutions.
–2 **Weegy:** The inequality -2 **User:** What are the solutions of the inequality? Graph the solutions.
b – 4 > 4
A. b –8
C. b >0
D. b > 8
**Weegy:** b ? 4 > 4
Adding 4 to both sides gives:
b > 8 (B). **User:** Suppose U = {–10, –6, –2, 0, 3, 5} is the universal set and T is the set {–10, –6, 0}.
What is the complement of set T?
A. {–2, 3, 5}
B. {–10, –6, 0}
C. {–6, –2, 0, 3, 5}
D. {0, 3, 5} (More)

Question

Not Answered

Updated 4/6/2014 10:03:02 AM

2 Answers/Comments

In the following situations, is there likely to be a correlation? If so does the correlation reflect a causal relationship? Explain. the average daily winter temperature and your heating bill
A. There is a positive correlation. The higher the average daily winter temperature the higher your heating bill.
B. There is a negative correlation and a causal correlation. The higher the average daily winter temperature the lower your heating bill.
C. There is no correlation.
D. There is ...**Weegy:** There is a negative correlation and a causal correlation. The higher the average daily winter temperature the lower your heating bill. (More)

Question

Expert Answered

Updated 4/5/2014 11:33:13 AM

0 Answers/Comments

28,201,639

questions answered

There are no comments.